(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The translation of literary works has always been a complex and multilayered process, especially when it comes to the masterpieces of iconic authors such as Mark Twain. His stories, imbued with humor, satire, and a distinct narrative voice, pose certain challenges and demand acute sensitivity from translators who attempt to render his works into other languages. Within this context, the translation of Mark Twain’s stories into Uzbek represents a rich field for linguistic analysis, touching upon diverse aspects such as syntax, lexicon, style, pragmatics, and cultural adaptation.